Array-based pharmacogenomics of molecular-targeted therapies in oncology - Sanoudou, D.; Mountzios, G.; Arvanitis, DA; Pectasides, D. (Pharmacogenomics JPharmacogenomics JPharmacogenomics J, 2012)
The advent of microarrays over the past decade has transformed the way genome-wide studies are designed and conducted, leading to an unprecedented speed of acquisition and amount of new knowledge. Microarray data have led to the identification of molecular subclasses of solid tumors characterized by distinct oncogenic pathways, as well as the development of multigene prognostic or predictive models equivalent or superior to those of established clinical parameters. In the field of molecular-targeted therapy for cancer, in particular, the application of array-based methodologies has enabled the identification of molecular targets with 'key' roles in neoplastic transformation or tumor progression and the subsequent development of targeted agents, which are most likely to be active in the specific molecular setting. Herein, we present a summary of the main applications of whole-genome expression microarrays in the field of molecular-targeted therapies for solid tumors and we discuss their potential in the clinical setting. An emphasis is given on deciphering the molecular mechanisms of drug action, identifying novel therapeutic targets and suitable agents to target them with, and discovering molecular markers/signatures that predict response to therapy or optimal drug dose for each patient.
Sanoudou, DMountzios, GArvanitis, D APectasides, DengResearch Support, Non-U.S. Gov'tReview2012/01/18 06:00Pharmacogenomics J. 2012 Jun;12(3):185-96. doi: 10.1038/tpj.2011.53. Epub 2012 Jan 17.
Keywords: *Economics, Pharmaceutical; *Molecular Targeted Therapy; *Oligonucleotide Array Sequence Analysis; *Precision Medicine; Animals; Antineoplastic Agents/*therapeutic use; Drug Resistance, Neoplasm; ErbB Receptors/antagonists & inhibitors/genetics; Gene Expression Profiling/*methods; Genetic Testing; Humans; Neoplasms/*drug therapy/genetics/metabolism; Patient Selection; Protein Kinase Inhibitors/*therapeutic use; Proto-Oncogene Proteins c-kit/antagonists & inhibitors/genetics; Receptor, ErbB-2/antagonists & inhibitors/genetics; Signal Transduction/drug effects; Treatment Outcome